The treatment of innocence by Marvell in "The picture of little T.C. in a prospect of flowers" - Castro Hidalgo, María de los Ángeles (2021)
Andrew Marvell (England, 1621-78) is a metaphysical poet that dealt eith a theme that according to H. R. Swardson can be called presexual or nonsexual innocence.